The Digital Glocalization of Entertainment New Paradigms in the 21st Century Global Mediascape - Sigismondi, Paolo; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
In this volume, Paolo Sigismondi explores the dynamics of global media and entertainment, specifically analyzing the implications of the global rise of non-scripted entertainment (as reality TV programs) and the impact and consequences of the Information and Communication Technology (ICT) revolution on the content, delivery platforms, and overall business models of the media and entertainment landscape. This work aims at bridging the gap between media theories and industry practices in a rapidly evolving global mediascape, building on scholarship in the field and enriched by case studies and insights from business practice. This work demonstrates that the paradigms of the landscape are shifting, introducing the digital “glocalization” of entertainment, through which successful media crossing national and cultural borders incorporate both global and local features. Key questions raised include: Is the ICT revolution an example of disruptive technology for the global media and entertainment industry? Is the existing status quo challenged, and in, particular Hollywood’s global leadership? What are the global entities emerging as Hollywood’s main competitors in this technologically evolving landscape? Sigismondi argues that as new players are entering the field, new threats to Hollywood’s dominance are emerging. The global leaders in non-scripted entertainment, for example, are European-based global entities operating outside the Hollywood system. Meanwhile, the ICT revolution is modifying the contours and boundaries of the global mediascape. Sigismondi’s approach provides unique insight into how the forces of technology and globalization are transforming television, cinema, and online entertainment.
Keywords: Industrial management; Media Management